Successful intervention of meningomyelocele associated with type 2 Arnold Chiari malformation and hydrocephalus – A case report - Vijay Baburao Sonawane; V Kotrashetti; Kapil Bainade; Saniya Sroa; Shuchi Bhatarkar (Indian Journal of Child Health, 2021)
Myelomeningocele, also known as open spina bifida, is characterized by non-closure of neural tube during embryonic development causing herniation of meninges and spinal cord through the vertebral defect. The risk of recurrence after one affected child is 3–4% and increases to 10% after two affected children. Meningomyelocele may rarely also be associated with Arnold Chiari malformations and hydrocephalus. However, most cases of Arnold Chiari malformation may remain asymptomatic.